Renewable Energy Consumption and Economic Growth: Evidence from Vietnam - Clottey, Samuel Attuquaye; Sun, Huaping; Amissah, Joshua Clifford Kofi; Mkumbo, Rebeca Nasolwa (European Scientific Journal, ESJ, 2018)
This paper contributes to the existing voluminous research on energy and growth providing a dynamic and comprehensive effect of investing in clean energy and it consequences on economic growth employing the ADRL modus operandi to co-integration to estimate the reality of co-integrating among the series in the long run. The analytical tests were realized utilizing the maximum lags explicitly chosen by estimating the series at level and confirming the stability of the unrestricted VAR model. The result establishes co-integration among the variables in the long run finding an inverse relationship between alternative and nuclear energy consumption and economic growth. The other indicator of clean energy that is electricity power consumption indicates a positive significant relationship with economic growth. Further we conclude that there is a bidirectional causal relationship between these two indicators and economic growth in the long run. This endorses the prospective benefit of Vietnam to invest in clean energy.